The Role of the Internet and Digital Technology on the Status of Workers with Disabilities in Central Sulawesi - Prasojo, Naufal Anhar; Kartiasih, Fitri (Quantitative Economics Journal, 2025)
Creating decent jobs for persons with disabilities makes workers with disabilities ready to compete in the labor market. Along with the times, the role of the internet and technological developments have reached a very rapid level which can help determine the status of workers with disabilities. Apart from the influence of the internet and technology there are other demographic factors that affect the status of workers with disabilities. The purpose of this research is to look at an overview of workers with disabilities from several factors and analyze the influence of internet technology and other variables on the status of workers with disabilities in Central Sulawesi Province. The method used is binary logistic regression analysis. The results of the study found that the role of the internet and technology greatly influenced the status of disabled workers during normal circumstances and during a pandemic. However, there is a decrease in the odds ratio due to the pandemic factor. The use of the internet and digital technology increase the chance for persons with disabilities to work in the formal sector.